The Influence Of Brand Image On Consumer Decisions In Ordering Aqiqah Catering At Ananda Aqiqah, Pekanbaru City - Edi Haryono; Imam Imam (Journal of Islamic Banking, Economics and Finance, 2026)
The increasingly competitive business world has made brand image a crucial factor influencing consumer decisions when choosing a product or service. Brand image not only reflects product quality but also builds customer perception, trust, and loyalty. Companies that are able to build a strong brand image have a distinct advantage in winning the hearts of consumers. Purchasing decisions are the result of a complex consideration process, where consumers choose products that align with their needs, preferences, and values. In this context, brand image plays a significant role in influencing consumer perceptions of the quality, reliability, and value of a product or service. The more positive the brand image embedded in consumers' minds, the more likely they are to make a purchase. The results of this study, based on the results of a simple linear regression analysis, obtained a constant (a) of 17.379, meaning that when the brand image is absent or zero, the decision to order vectorvg vector aqiqah is still obtained at 17.379. Meanwhile, the relationship between brand image and purchasing decisions is positive, as evidenced by the regression coefficient (b) of 0.594, which means that every one-unit increase in brand image will increase the decision to order the aqiqah vector by 0.594. Based on the results of the T-Test (Partial), the calculated t value (9.884)> t table (1.980) is obtained. Therefore, H0 is rejected and Ha is accepted. This means that brand image has a significant influence on consumer purchasing decisions in ordering Ananda Aqiqah Catering. Based on the results of the study, the coefficient of determination (R2) value is 0.771, where this figure indicates that brand image influences consumer purchasing decisions in ordering Ananda Aqiqah Catering by 77%. While the remaining 23% is influenced by other variables not examined in this study. The recommendation in this study is that the management should further improve the brand image of Ananda Aqiqah Catering to make it more attractive to high-status consumers.